Hypertrophic scar after cleft lip repair: Review of the current treatment - Córdova-Aguilar, Alberto (2020)
Cleft lip -with or without cleft palate- is the most frequently reported facial congenital malformation in the world that requires surgery -cheiloplasty- to be corrected. Unfortunately, the hypertrophic scar after cheiloplasty is a common result that negatively affects the patient, their social environment and even the specialists, because to date there is no specific treatment. In order to know the current status of the treatment of this problem, a literature review was conducted since 2000 in the different databases. It was found that the treatment and prevention options are similar: primary closure of the wound without tension, adhesive tape of microporous paper, injection of intralesional corticoid, silicone sheet or gel, flavonoid gel, and laser. It was concluded that the treatment of the hypertrophic scar after cheiloplasty is still unsatisfactory and the research is limited since it is not a replicable pathology in animal models.